Study of Rolling Resistance and Maneuvering Characteristics of a Prototype Vehicle Under Variations in Negative Camber Angle - Haidzar Nurdiansyah; Rika Dwi Hidayatul Qoryah; Andi Sanata; M Fahrur Rozy Hentihu; Santoso Mulyadi; Rahmad Fajar Zaini (International Journal of Integrated Engineering, 2026)
In the development of energy-efficient vehicles, two aspects that are often the main concerns are the magnitude of rolling resistance and cornering stability. High rolling resistance can hinder the efficiency of vehicle speed. While the appropriate turning radius setting can maintain vehicle control when maneuvering. This study aims to determine how the tire camber angle can affect both aspects in prototype category vehicles for energy-efficient vehicle competitions. The test was conducted using the Rolling Resistance Test Rig and field testing by varying the negative camber angle by -1°, -2°, and -3°. The test results show that a camber angle of -1° produces an average rolling resistance value of 2.61 N and a tendency to oversteering maneuvers. At a camber angle of -2°, the rolling resistance increases to 2.78 N and the vehicle still shows symptoms of oversteering. While at a camber angle of -3°, the highest rolling resistance is 3.15 N with more balanced and neutral steering. This shows that, the more negative the camber angle can increase rolling resistance, but results in better maneuvering stability, although in this study it was limited to a maximum camber angle of -3°.